RESPONS MENTIMUN JEPANG (Cucumis sativus L.) Var. Roberto TERHADAP PERENDAMAN BENIH DENGAN GIBERELIN (GA3) DAN BAHAN ORGANIK HASIL FERMENTASI (BOHASI) - Suryaman Birnadi (JURNAL ISTEK, 2017)
An experiment was conducted to study the effect of plant growth regulator gibberellin (GA3) and banana stem bohasi on growth and results of Japanese Cucumber (Cucumis Satifus L. Var Robberto) has been done in Tolengas, Sumedang since March 2015 to May 2015. Using Randomized Group Design factorial with three replications consisting of two factors. The first factor is the appropriation of plant growth regulator gibberellin (GA3) which consists of: (1) 0 ppm; (2) 100 ppm; (3) 200 ppm; (4) 300 ppm. The second factor is banana stem bohasi consisting of: (1) 0 t ha-1 (2) 10 t ha-1 (3) 20 t ha-1 with the observation parameters plant height, number of leaves, the weight of fresh stover, the weight of dry stover and the weight of the fruit crop on each plant. The results showed that no interaction between the administration of growth regulator gibberellin (GA3) and banana stem bohasi fertilizer on all parameters of observation. Best effect is shown by the plants treated with growth regulator gibberellin (GA3) concentration of 200 ppm (g2) and banana stem Bohasi manure 20 t ha-1 parameter on plant height, number of leaves, the weight of fresh stover and the weight of the fruit crop on each plant.